Command of Banking Products in the Chosen Social Groups - Benachir, Alicja (Journal of Finance and Financial Law, 2016)
The point of professed unfamiliarity of banking products and theirs mechanism is often pointed as a cause of a plethora of wrong decisions related to management of funds of banking clients and financial institutions. The aim of this paper is to evaluate awareness about bank products of a group of retail customers of banks. The author assumed that financial knowledge of Poles is low, what has been not confirmed by carried out an empirical study.